Ajuste de modelos no lineales para caracterizar el crecimiento de bovinos hereford y salers. - Domínguez Viveros, Joel; Ortega Gutiérrez, Juan íngel; Rodríguez Almeida, Felipe Alonso; Callejas Juárez, Nicolás; Aguilar Palma, Nelson Guadalupe; Santillán Moreno, Eduardo (Revista Científica de la Facultad de Ciencias Veterinarias, 2014)
Ver resumen pdf.